EFEKTIVITAS KOMUNIKASI INTERPERSONAL TERHADAP PEMAHAMAN MATERI PADA PERKULIAHAN DARING (Studi Pada Mahasiswa Ilmu Komunikasi Universitas Ratu Samban) - Susanto, Prio; Astuti, Linda; Indrianti, Henni (SENGKUNI Journal (Social Science and Humanities Studies), 2025)
During the Covid-19 pandemic, Ratu Samban University implemented an online learning system. This research aims to obtain empirical evidence of whether or not there is an influence of interpersonal communication effectiveness on understanding the material in online classes for Communication Science students at Ratu Samban University, North Bengkulu. This research is a quantitative descriptive study with data collection techniques through the distribution of questionnaires. The results of this study indicate that interpersonal communication is effective in understanding the material in online classes, thus the working hypothesis of the research is accepted. The interpersonal communication of Communication Science students at Ratu Samban University shows an effective value, however, in understanding the material in online classes, Communication Science students at Ratu Samban University show a low value.